Swedberg's Swensk Ordabok (morphology, rudimentary) - Språkbanken Text (University of Gothenburg, 2024)
Swedberg's Swensk Ordabok (morphology, rudimentary)

Swedbergs Swensk Ordabok (morfologi, f.n. rudimentär)
Swedbergs Swensk ordabok (morfologi, f.n. rudimentär)
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik